STRATEGI INTERVENSI DAN PENDEKATAN PENGASUHAN ANAK DENGAN ADHD : A LITERATURE REVIEW - Yakin, Muhamad Aminul; Pabela, Tiara; Aldo; Nasution, Muhammad Fahri (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
Attention Deficit Hyperactivity Disorder (ADHD) is a developmental disorder characterized by symptoms of inattention, hyperactivity, and impulsivity, which significantly impact a child's adaptive functioning across family, school, and social contexts. This literature review aims to examine various intervention strategies and parenting approaches that are effective in managing children with ADHD. Findings indicate that multimodal interventions combining pharmacotherapy and behavioral therapy are the most clinically recommended. Moreover, active parental involvement through behavior-based parenting skill training has been shown to improve children's emotional and behavioral regulation while reducing parental stress. Consistent, supportive, and responsive parenting practices play a crucial role in the social-emotional development of children with ADHD. Thus, intervention strategies that holistically involve the family system serve as key approaches to enhancing the long-term quality of life for children with ADHD. Keywords: ADHD, children, intervention, parenting, behavioral therapy.